Exploring Teachers’ Challenges in Implementing Interactive Speaking Strategies for Low-Proficiency EFL Learners: A Qualitative Case Study - Iga Rahman; Syarifuddin Dollah; Muhammad Tahir (FOSTER: Journal of English Language Teaching, 2026)
This study explores the challenges faced by teachers in implementing interactive speaking strategies for low-level students in the Speaking for Teens classes at Britania School of English (BSE). A qualitative case study design was employed to examine teachers’ experiences in real classroom contexts. The participants consisted of three English teachers, supported by nine students from three classes. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using data condensation, data display, conclusion drawing, and thematic analysis. The findings revealed that teachers encountered several challenges during interactive speaking activities, including noise distractions caused by classroom arrangements, student fatigue during after-school sessions, difficulties in understanding instructions, classroom management issues during games and group work, and the need to adjust activities to match students’ low English proficiency. These challenges were influenced by environmental, affective, linguistic, and pedagogical factors. The study concludes that difficulties in implementing interactive speaking strategies stem largely from contextual and learner-related factors rather than weaknesses in the strategies themselves; therefore, teachers need to carefully plan, adapt, and manage interactive activities by considering students’ proficiency levels, classroom conditions, and emotional readiness to support effective speaking instruction.